Analysis of Basic Laboratory Skills of Science Education Students Using Pictorial-Based Instruments - Rahayu, Dea Santika; Muqtada, Moh. Rikza (Chemistry Education Department, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga, 2023)
Laboratory skills are an important aspect of natural sciences in schools and higher education, often linked to psychomotor aspects of learning. Several studies have developed several methods that can be used to evaluate laboratory skills, for example, the use of observation sheets equipped with rubrics. However, often using this method requires a longer learning time. Therefore, there is a need for research that examines how to evaluate students' basic laboratory skills. This research aims to analyze students' basic laboratory skills using pictorial-based instruments. This research method uses descriptive qualitative. This instrument is equipped with pictures that provide visualization. The basic laboratory skills are focused on experiments on making standard solutions from solids, making standard solutions from concentrated solutions, and acid-base titrations. Based on the analysis, it was found that the basic laboratory skills of science students in the experiment of making standard solutions from solids contained six basic skills, including selecting tools, weighing solids, transferring solids into a beaker, putting them in a volumetric flask, marking the solution, reading the meniscus mark. In the experiment of making a standard solution, there are five basic skills, namely selecting tools, taking the stock solution, transferring it into a volumetric flask, marking the solution, and reading the meniscus mark. The titration experiment consists of 8 skills, including selecting equipment, taking the analyte solution, taking the titrant solution, adding a titration indicator, using the titration technique, observing the endpoint of the titration, reading the meniscus, and calculating the solution's concentration.